Synthesis of Regioselectively Protected Protocatechuic Acid Derivatives by Biomimetic Transformation of Quinic Acid - Cristiana Melchioni; Francesco Bonadies; Armandodoriano Bianco (Molecules, 2000)
3- and 4-monoesterified protocatechuic acid methyl ester (5 and 7 respectively) have been synthesised from quinic acid by a high yields biomimetic rearrangement.